The drama of the American short story, 1800-1865 - Collins, Michael J. 1984- (Ann Arbor University of Michigan Press, 2016)
This book argues that to truly understand the short story form, one must look at how it was shaped by the lively, chaotic, and deeply politicized world of 19th-century transatlantic theater and performance culture. By resurrecting long-neglected theatrical influences on representative works of short fiction, Michael J. Collins demonstrates that it was the unruly culture of the stage that first energized this most significant of American art forms. Whether it was Washington Irving's first job as theater critic, Melville's politically controversial love of British drama, Alcott's thwarted dreams of stage stardom, Poe and Lippard's dramatizations of peculiarly bloodthirsty fraternity hazings, or Hawthorne's fascination with automata, theater was a key imaginative site for the major pioneers of the American short story. The book shows how perspectives from theater studies, anthropology, and performance studies can enrich readings of the short story form. Moving beyond arbitrary distinctions between performance and text, it suggests that this literature had a social life and was engaged with questions of circumatlantic and transnational culture. It suggests that the short story itself was never conceived as a nationalist literary form, but worked by mobilizing cosmopolitan connections and meanings. In so doing, the book resurrects a neglected history of American Federalism and its connections to British literary forms
Introduction: The Irving brothers at the Park Theatre, 1802 -- "No garden of thought, nor elysium of fancy": Washington Irving's The sketch-book of Geoffrey Crayon, Gent -- The rites of pure brotherhood: fraternalism and performance in Poe and Lippard -- "The rule of men entirely great": Richelieu, ritual, and republicanism in Melville's diptychs -- The "child of nature," or the "wonder of the age": Melville's child prodigies -- "Contending for an empire": performing sincerity in Hawthorne's New England -- Epilogue: Louisa May Alcott's theatrical realism.
Includes bibliographical references and index
Keywords: 1800-1899; National characteristics, American, in literature; Ritual in literature; Theater in literature; Performing arts in literature; Performance in literature; American fiction -- 19th century -- History and criticism; Short stories, American -- History and criticism; Rituel dans la littérature; Théâtre dans la littérature; Arts du spectacle dans la littérature; Rendement au travail dans la littérature; Roman américain - 19e siècle - Histoire et critique; Nouvelles américaines - Histoire et critique; PERFORMING ARTS - Theater - General; American fiction; Literature; National characteristics, American, in literature; Performance in literature; Performing arts in literature; Ritual in literature; Short stories, American; Theater in literature; Criticism, interpretation, etc; America -- In literature; Amérique - Dans la littérature; America